Determinan kemandirian keuangan daerah Kabupaten/ Kota di Provinsi Jambi - Afriyan Firmanda, Rido; Hodijah, Siti; Vyn Amzar, Yohanes (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Regional financial independence is a condition where the process of financing the implementation of a regional government is carried out independently using original regional income. This research aims to see and analyze the influence of capital expenditure, general allocation funds and special allocation funds on regional financial independence in Jambi Province in 2010-2021. The data used is secondary data with time series during the period 2010-2021. And the analysis method used is the Panel Data Regression Method. The research results show that at the f test (simultaneous), we can conclude that simultaneously the variables Capital Expenditure, General Allocation Funds and Special Allocation Funds have an effect on regional financial independence in Jambi Province. Viewed using the t test (partial), we can conclude that the capital expenditure variable has a negative and significant effect on regional financial independence and the general allocation fund has a positive and insignificant effect on regional financial independence, while the special allocation fund variable has a positive and significant effect on regional financial independence.